2017
DOI: 10.1080/01658107.2017.1304425
|View full text |Cite
|
Sign up to set email alerts
|

An Estimation of the Risk of Pseudotumor Cerebri among Users of the Levonorgestrel Intrauterine Device

Abstract: Because of a previous association of pseudotumor cerebri (PTC) with levonorgestrel, we wished to evaluate the use of levonorgestrel-eluting intrauterine devices ("levonorgestrel intrauterine systems", LNG-IUS) in our University of Utah and Rigshospitalet PTC patients. In our retrospective series, PTC prevalence was approximately 0.18% and 0.15% in the LNG-IUS population versus 0.02% and 0.04% in the non-LNG-IUS population (Utah and Rigshospitalet, respectively), with no significant differences in PTC signs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…The results from some of these studies were underpowered because of a small number of events [1,2,12], leading to wide CIs. Other studies did not control for all potential confounders including age and BMI [5,6]. One study [6] undertook a descriptive study where two sets of controls, one from Utah and one from Denmark, were used to generate ORs [7.70 (95% CI 3.7–16.0) and 3.91 (95% CI 1.89–8.06, respectively, for Utah and Danish controls].…”
Section: Discussionmentioning
confidence: 99%
“…The results from some of these studies were underpowered because of a small number of events [1,2,12], leading to wide CIs. Other studies did not control for all potential confounders including age and BMI [5,6]. One study [6] undertook a descriptive study where two sets of controls, one from Utah and one from Denmark, were used to generate ORs [7.70 (95% CI 3.7–16.0) and 3.91 (95% CI 1.89–8.06, respectively, for Utah and Danish controls].…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic intracranial hypertension (IIH) is a condition of unclear etiology that typically occurs in young, obese women in the reproductive years, which causes headaches, papilledema, and possible vision loss. 15 Some prior studies, largely consisting of case reports, 610 suggest a link between oral contraceptive pills (OCPs) and an increased risk of intracranial hypertension, 7, 8, 1115 while other studies have not shown this association. 2, 1619 There are also a few studies suggesting a possible association between IIH and non-OCP hormonal contraceptives, such as the levonorgestrel intrauterine device (IUD), contraceptive implants, and medroxyprogesterone.…”
Section: Introductionmentioning
confidence: 99%
“…2, 1619 There are also a few studies suggesting a possible association between IIH and non-OCP hormonal contraceptives, such as the levonorgestrel intrauterine device (IUD), contraceptive implants, and medroxyprogesterone. 6, 911, 15, 20, 21 The connection between hormonal contraceptives and IIH, therefore, remains controversial among clinicians and the general public. Any study evaluating the connection between hormonal contraceptives and IIH must take into account possible bias from the demographics of the disease, since women of childbearing age are the most likely population to use contraceptives.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 One recent descriptive study demonstrated an increase in risk with intrauterine levonorgestrel (IL) and PTCS. 23 The study used data from Utah and Denmark and showed an increased odds ratio of 7.70 (95% CI: 3.7-16.0) and 3.91 (95% CI: 1.89-8.06). 23 One limitation of the study was difficulty discerning the timing of the onset of PTCS in relation to IL use.…”
Section: Discussionmentioning
confidence: 99%